Jewelry Set Design Based on the Adaptation of the Keris Shape - Chairunnisa Rania Humaira; Edwin Buyung Syarif; Fajar Sadika (Jurnal Teknik Industri: Jurnal Hasil Penelitian dan Karya Ilmiah dalam Bidang Teknik Industri)
Jewelry is a form of cultural and artistic wealth. Apart from that, jewelery products have also spread to the global market in various major countries, this is evident from data on jewelery exports in Indonesia which have increased by up to 24.21% even in the midst of the Covid-19 pandemic. In modern life, of course, there are many women who want to beautify themselves with jewelery because the main users of this jewelery are women, but the jewelery that we often see has simple geometric shapes, therefore a strategy is needed to implement cultural values into everyday product. One form of culture that we have is the keris. Keris is a kind of dagger that functions as a weapon or spiritual object. In addition, the keris is also popular as a collection item that has high value from an aesthetic point of view because it has interesting artistic elements. The artistic elements contained in the keris can also be implemented into products that we use every day, namely jewelry. This writing aims to design jewelry by taking several parts of the keris which will be adapted into jewelry forms in order to provide innovation in the form of jewelry that has a novelty value without losing the characteristics of the keris.